ผลของการสนับสนุนการปฏิบัติตามหลักพุทธธรรมต่อความผาสุกทางจิตวิญญาณในผู้สูงอายุที่เป็นโรคมะเร็งอวัยวะสืบพันธุ์สตรี โรงพยาบาลมหาราชนครเชียงใหม่ - อุบล บัวชุม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Spiritual well-being is an important indicator of quality of life in patients with gynecological cancer, so supporting their spiritual well-being is also important. This quasi-experimental research aimed to examine the effect of supporting Buddhist doctrine practices on spiritual well-being among elderly patients with gynecological cancer. Participants included 40 elders with gynecological cancer hospitalized at gynecological wards 3 and 4, Maharaj Nakorn Chiang Mai Hospital, during September 2013 to April 2014. The participants were purposively assigned into two groups. The control group, hospitalized during September 2013 to December 2013, received usual care. The experimental group who were hospitalized during January 2014 to April 2014 received supported Buddhist doctrine practices. Data were collected using the Spiritual Well-Being of Lung Cancer Elders Scale developed by Nongyao Kuntamun (2546) with Cronbach alpha’s coefficient of .83. Data were analyzed using descriptive statistics and t-test. The results of this study revealed that: 1. After support to practice Buddhist doctrine the spiritual well-being of elders with gynecological cancer was statistically higher than prior to receiving this support (p<0.01). 2. The spiritual well-being of the elderly participants support to practice Buddhist doctrine was statistically higher than that of the elders receiving usual care (p<0.01). The results of this study indicate that nurses who care for elderly patients with gynecological cancer should support practicing Buddhist doctrine to enhance patients, spiritual well-being.